2022
DOI: 10.1002/aenm.202201370
|View full text |Cite
|
Sign up to set email alerts
|

Machine‐Learning‐Based Exploration of Bending Flexoelectricity in Novel 2D Van der Waals Bilayers

Abstract: Accurate examination of electricity generation stemming from higher‐order deformation (flexoelectricity) in 2D layered materials is a highly challenging task to be investigated with either conventional computational or experimental tools. To address this challenge herein an innovative and computationally efficient approach on the basis of density functional theory (DFT) and machine‐learning interatomic potentials (MLIPs) with incorporated long‐range interactions to accurately investigate the flexoelectric ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Machine-learning-based algorithms for phononic property calculations have been developed and are now utilized frequently as a robust and effective alternative to DFT simulations. [51][52][53][54][55][56] The most appealing solutions at the moment are those that rely on machine learning and are developed from machine-learning interatomic potentials (MLIP), which have DFT accuracy but MD (molecular dynamics) efficiency and enable the bridge between first principles based models and continuum models. By using the MLIP technique, Li et al 57 predicted the thermal conductivity of cubic boron arsenide and demonstrated its dependability in obtaining interatomic force constants.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Machine-learning-based algorithms for phononic property calculations have been developed and are now utilized frequently as a robust and effective alternative to DFT simulations. [51][52][53][54][55][56] The most appealing solutions at the moment are those that rely on machine learning and are developed from machine-learning interatomic potentials (MLIP), which have DFT accuracy but MD (molecular dynamics) efficiency and enable the bridge between first principles based models and continuum models. By using the MLIP technique, Li et al 57 predicted the thermal conductivity of cubic boron arsenide and demonstrated its dependability in obtaining interatomic force constants.…”
Section: Computational Detailsmentioning
confidence: 99%
“…It was found that italicWSi2N4, italicCrSi2N4, and italicMoSi2N4 monolayers show high piezoelectric coefficients while italicCrSi2N4, and italicMoSi2N4 display high lattice thermal conductivity and mechanical strength. Javvaji et al [19] established that generating electricity stemming from flexoelectricity in 2D layered materials is difficult and to answer this challenge, they introduced an efficient approach based on density functional theory and machine learning inter‐atomic potentials for accurate investigation of 2D van der Waalis bilayers.…”
Section: Introductionmentioning
confidence: 99%
“…This motivates the development of computationally feasible approaches in this realm. A recently emerging third alternative in literature to this end is employing data-driven surrogate models devising machine learning, see, e.g., [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33] and the references therein. Deploying the training costs offline materializing simulation or experimental data, these models surpass conventional rule-based approaches by drastically reducing the computational cost required during the prediction phase [34,35,36].…”
Section: Introductionmentioning
confidence: 99%